Restructuring federal climate research to meet the challenges of climate change [electronic resource] - Center for Studies of Behavior and Development (US); National Academies Press (US); National Research Council (US) . Committee on Strategic Advice on the US Climate Change Science Program; National Research Council (US) . Division on Earth and Life Studies (Washington, DC : National Academies Press, 2009)
With effective climate change mitigation policies still under development, and with even the most aggressive proposals unable to halt climate change immediately, many decision makers are focusing unprecedented attention on the need for strategies to adapt to climate changes that are now unavoidable. The effects of climate change will touch every corner of the world's economies and societies; adaptation is inevitable. The remaining question is to what extent humans will anticipate and reduce undesired consequences of climate change, or postpone response until after climate change impacts have altered ecological and socioeconomic systems so significantly that opportunities for adaptation become limited. This book summarizes a National Research Council workshop at which presentations and discussion identified specific needs associated with this gap between the demand and supply of scientific information about climate change adaptation
1. Restructuring the climate change science program -- 2. Future priorities -- 3. Appendixes: A. Examples of bills with a significant climate change component considered in the 110th congress -- 4. B.U.S. climate change science program -- 5. C. Process for identifying
Description based on print version record
Includes bibliographical references (p 123-145)
Also available via the World Wide Web
Keywords: Climatic changes -- Research -- United States; Climatic changes -- Risk management -- United States; Global warming -- Research -- United States